Metode Eksperimental untuk Meningkatkan Minat Belajar PAI di SDN 3 Kelapa Sawit - Al Mubarok, Akhmad Zidni; Nasrulloh, M.; Fatimah, Siti; Subarkah, Imam; Rinawati, Atim; Trisnawati, Oky Ristya (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study aims to determine the increase in interest in learning Islamic Religious Education through experimental methods at SDN 3 KLOPO SAWIT. This type of research is classroom action research. Data collection techniques are carried out by observation, interviews, and documentation. Based on the results of the study as previously explained, it can be concluded that the implementation of the Experimental method in Islamic Religious Education learning has a significant influence on student learning outcomes. This is because the Experimental method creates meaningful learning in forming thinking skills by trying new things by conducting experiments and allowing students to directly explore the material being taught. The method used has been proven to increase student interest in learning, namely in cycle 2 students experienced an increase in student interest in learning which was better than cycle 1. With evidence in cycle I there was an increase of only 69%, while in cycle 2 it had reached an increase of 86%.